Unlearning - Buddhism and the Public Understanding of Buddhism The Print Media and the Public Understanding of Buddhism - Harris, Elizabeth June (Journal of the British Association for the Study of Religions, 2023)
This paper focusses on two popular book projects that sought to communicate Buddhism’s variety and complexity to non-specialists. The first emerged from a radio series that the author was asked to write and present for the BBC World Service in the mid-1990s, entitled The Way of the Buddha. A book from the series followed, published by Oneworld. The second was an edited book that also slotted into a series, published by Equinox - Buddhism in 5 Minutes. The paper is an exercise in self-reflexivity, in the context of two demands that are placed on academics within religious studies. The first of these is the government’s insistence that academic research should have an impact on ‘the economy, society, culture, public policy or services, health, the environment or quality of life’. The second is the lack of religious literacy within society and the demands placed on academics working within religious studies to address it. This short paper will, therefore, concentrate on the aims, method, structure and content of each book in the light of these demands. It will also explore the potential of such projects and the issues they raise for the discipline of religious studies and our role as academics.